EVALUATING THE ROLE OF FORESTED AREA, AGRICULTURAL LAND, ENERGY CONSUMPTION AND FOREIGN DIRECT INVESTMENT ON CO2 EMISSIONS IN INDONESIA - Chia--Guan Keh; Yan-Teng Tan; Siu-Eng Tang; Jia-Jia Sim; Chin-Yu Lee, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Environmental concerns have steadily gained attention as the economy has grown more rapidly. This ultimately impedes the growth of a high-quality economy. Several factors, namely forested area, agricultural land, energy consumption and foreign direct investment, have contributed significantly to economic expansion while simultaneously deteriorating the environment in the short and long run. Hence, this study empirically examines the effect of forested area, agricultural land, energy consumption and foreign direct investment on CO2 emissions in the case of Indonesia from 1990 to 2020 by employing the autoregressive distributed lags (ARDL) approach. The results indicate that forested area negatively and significantly impacts CO2 emissions in the short and long run. However, agricultural land, energy consumption and foreign direct investment positively influence CO2 emissions in the long run. Moreover, agricultural land and foreign direct investment demonstrate a negative relationship with CO2 emissions, whereas energy consumption positively affects CO2 emissions in the short run. Thus, the results are insightful for policymakers to develop efficient strategies to reduce carbon emissions and eradicate environmental deterioration in Indonesia.